El acceso universal al agua potable. La experiencia peruana - Cairampoma Arroyo, Alberto (2016)
The present article aims to review the development of universal access to potable water in Peru, for this, firstly it analyses the regulations applicable to potable water and sanitation, the main actors of the activity and universal access policy. Subsequently, it explains how the access of all users to potable water in urban and rural areas, respectively is planned.